Heteronormativnost in regulacije rodnosti - Mencin Čeplak, Metka (Annales. Series historia et sociologia, 2013)
Article is based on Foucault's thesis that regulation of sexuality is one of the key strategies of biopolitics. Author analyzes the role of heteronormativity in population politics and in researching origins of gender differences and sexual orientation. Empirical analysis is based on the data collected from political discussions on birth-rate, legal regulation of pregnancy and family and partner relationship rights, and from researches that tend to prove biological basis of gender differences and sexual orientation. Analysis confirms the hypothesis that behavioural conformity with patriarchal gender and sexual norms is one of the key criteria of persons worth, and one of the key criteria of defining population categories entitled to benefits and rights guaranteed by the state (e.g. artificial insemination, rights and benefits concerning family and partner relationships). Author points out that some researches in the field of medicine and genetics (discovery of human genome) support discriminatory regulations in accordance with the article topic, she mainly problematizes the thesis that the sexual orientation is biologically determined, and the patologization of supposedly biological causes of the same-sex sexual orientation. Article warns that the patologization of the same-sex sexual orientation legitimized by science and scientific discourses implicitly legitimizes eventual eugenic practices. Namely, patologization confirms wide spread conviction that same-sex sexual orientation is anomaly that should be prevented, corrected, or that its potential damage to individuals (marginalization and discrimination) and to communities (negative impact on fertility rate and subversion of social order based on gender dichotomies and heterosexuality) should be reduced in some way or another. It opens up opportunities for enhancement eugenic practices - in the name of reproductive freedom and protection of supposed childrens interest.
Keywords: Discrimination; Diskriminacija; Eugenics; Evgenika; Genetics; Genetika; Homoseksualnost; Homosexuality; istospolna partnerska skupnost